Al-Qur'an Therapy for Mothers in Childbirth: Living Qur'an Study at PMB Nina Yunita, Mlarak-Ponorogo - Mahmud Rifaannudin; Fadly Rahman Akbar; Muhammad Badrun (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
Problems that are often experienced by mothers giving birth are anxiety and fear of pain, so giving birth to children becomes a frightening specter because they doubt the safety of the baby and himself. To relieve this anxiety, it can be done by means of pharmacology and non-pharmacology or therapy. One way of therapy is with murattal al-Qur'an, as a form of Living Quran to accompany childbirth. The purpose of this study was to determine the understanding brought by the mother giving birth when the chanting of the Qur'an was heard accompanying the delivery process. This is a type of field research with a qualitative research approach, located at PMB Nina Yunita in Gandu Village, Kec. Mlarak, Ponorogo Regency. Data collection methods used in this research are observation, interviews and documentation. The result of this research is the influence of an understanding of the Qur'an by a living Qur'an actor, namely the opinion that the Qur'an is a book of guidance, a book of instructions, with which it can be seen what is right and what is wrong, as well as to regulate actions. humans to their creators, so that with a good understanding of the Qur'an it brings a feeling of relaxation and comfort when heard, then provides convenience in the delivery process and becomes the key to safety for mothers and babies during childbirth. Key word: therapy, murattal, Qur’an, childbirth Abstrak Permasalahan yang sering dialami oleh ibu melahirkan adalah rasa cemas dan takut akan rasa sakit, sehingga melahirkan anak menjadi momok menakutkan karenaraguakan keselamatan bayi dan dirinya. Untuk meredakan kecemasan tersebut bisadengan cara farmologidan non farmakologi atau terapi. Salah satu caraterapinyayaitudenganmurattal al-Qur’an, sebagai bentuk Living Quran untuk mengiringi persalinan. Tujuan penelitian ini adalah untuk mengetahui pemahaman yang dibawa oleh ibu melahirkan ketika diperdengarkan lantunan al-Qur’an dalam mengiringi proses persalinan. Ini merupakan jenis penelitian lapangan dengan Pendekatan penelitian kualitatif, berlokasi di PMB Nina Yunita di Desa Gandu, Kec. Mlarak, Kab Ponorogo. Metode pengumpulan data yang digunakan dalam penelitian ini adalah Observasi, wawancara dan Dokumentasi. Hasil dari peneltian ini adalah adanya pengaruh pemahaman tentang al-Qur’an oleh seorang pelaku living Qur’an, yaitu berpendapat bahwa al-Qur’an merupakan kitab pedoman, kitab petunjuk, dengannya dapat terlihat yang haq dan yang batil, juga untuk mengatur perbuatan manusia terhadap penciptanya, sehingga dengan pemahaman yang baik akan al-Qur’an mebawa perasaan rileks dan nyaman ketika diperdengarkan, kemudian memberikan kemudahan dalam proses persalinan dan menjadi kunci keselamatan untuk ibu dan bayi saat proses persalinan. Kata Kunci: terapi, murattal, Al-Qur’an, melahirkan